Epistemologi islam sebagai worldview asas ilmu, iman, dan amal bagi seorang pendidik - Krisna Wijaya (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This article tries to explain the fundamental basis in the epistemological scientific framework that builds the Islamic worldview for an educator who plays a strategic role in the world of education. This worldview of an educator must be clarified and built on concepts that are in accordance with Islamic religious values ​​because it will act as a principle of faith, knowledge, and charity for an educator when teaching his students. This is very important to discuss because seeing the conditions of today's modern era where challenges to thinking are very real are lurking in our world of education. The good and bad conditions of the world of education will be determined by educators, especially the worldview of educators themselves. Therefore, this is where the researcher tries to examine this by using the library approach method, where theoretical data can be found offline or online. The result of this discussion is that the concept of Islamic epistemology based on monotheism turns out to be a fundamental worldview for educators to have faith (soul), knowledge (mind), and charity (body) when teaching in the classroom.